2006
DOI: 10.1029/2005wr004364
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of permeability anisotropy using wavelet analysis

Abstract: [1] Wavelet analysis is an image analysis technique that can extract local information at multiple scales. Because of this capability, wavelet analysis can be used to identify dominant scales in statistically heterogeneous and anisotropic random fields. We develop and test a wavelet analysis method for identifying dominant scales and orientations in permeability fields and for identifying boundaries between regions with different dominant orientations. We evaluate three different wavelets (fully anisotropic Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…This pattern is consistent with the relationship between wavelet scales and periods for a periodic function [see Neupauer et al, 2006].…”
Section: Theoretical Evaluation Of Wavelet Measuressupporting
confidence: 69%
See 2 more Smart Citations
“…This pattern is consistent with the relationship between wavelet scales and periods for a periodic function [see Neupauer et al, 2006].…”
Section: Theoretical Evaluation Of Wavelet Measuressupporting
confidence: 69%
“…[22] In some prior applications of wavelet analysis [e.g., Li and Loehle, 1995;Neupauer et al, 2006], the GWS was found to be useful for identifying characteristic length scales. In these applications, the data were approximately …”
Section: Theoretical Evaluation Of Wavelet Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In two dimensions, analyses have also been conducted to identify anisotropic spatial variations of rainfall [19,20], rock composition [14,15], soil thickness, surface slope, and direct solar radiation [24], and permeability [29,42]. Wavelets have also been applied to upscaling of porous medium properties [7][8][9]28,[32][33][34]36].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for a property that displays periodic fluctuations, such as seasonal fluctuations in ice extent [17], the global wavelet spectrum (GWS), r 2 W ðaÞ ¼ A À1 R X jW f ða; bÞj 2 db, where A is the area of the domain, can be used to identify the period, T, of the fluctuations. The scale a max at which r 2 W ðaÞ attains its maximum value is related to the period T through the relationship T ¼ 2pa max = ffiffiffi 3 p [29]. The GWS has been used to identify characteristic length scales in some prior applications (e.g., [26,29]).…”
Section: Introductionmentioning
confidence: 99%